Emotional Regulation of Widows in Forced Marriages: An Experience from Madurese Women - Novia; Bawono, Yudho (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The purpose of this study was to determine the emotional regulation experienced by widows who have experienced forced marriage. This study involved 3 participants. Participant 1 was 22 years old, participant 2 was 21 years old, and participant 3 was 19 years old. Extracting data on research participants using semi-structured interviews. This study uses an Interpretative Phenomenological Analysis (IPA) approach. The data obtained were then analyzed using 7 steps in IPA, including: 1) Reading and re-reading; 2) Initial noting; 3) Developing emergent themes; 4) Arranging superordinate themes; 5) Proceed to the next case; 6) Look for patterns between cases; and 7) Arrangement of all superordinate themes. Themes that have similarities between research participants are then used to explain the experience and meaning of emotional regulation for widows who have experienced forced marriage. The results of this study indicate that a widow who has experienced forced marriage is able to regulate emotions by several processes, namely involving someone in taking an action or avoiding a situation to get something that is desired. Changing situations and diverting attention from unpleasant situations which aims to reduce the influence of emotions that arise. Keywords: emotional regulation, widows, forced marriage